Dual function antibody targeting αvβ3 and PD-L1 provide a promising strategy for solid tumor therapy - Li, Guixia; Li, Wenlei; Wang, Liuli; Bi, Yuxin; Wang, Yibo; Zheng, Xuemin; Hao, Ruijia; Yin, Yanchen; Yu, Yan; Mu, Huaibin; Li, Jian; Ma, Xiaohui; et al. (Frontiers in Immunology, 2026)
BackgroundThe inhibition of the PD-1/PD-L1 axis has exhibited significant advancements in cancer immunotherapy, improving patient outcomes in various cancers. However, the clinical efficacy of these monotherapies remains limited in many cases. Integrin αvβ3 has been identified as a positive regulator of PD-L1 expression and a critical contributor to cancer immune evasion. To address this, we developed a dual function antibody, B1451, that recognizes both PD-L1 and αvβ3 and evaluated its antitumor efficacy in pre-clinical models in vitro and in vivo.MethodsWe first analyzed the correlation between PD-L1 and αvβ3 expression, as well as the role of αvβ3 in modulating sensitivity to immunotherapy, using the TISIDB database. Subsequently, we designed and constructed a dual function PD-L1×αvβ3 antibody (B1451) by conjugating an integrin αvβ3-binding peptide to the C-terminal of the heavy chain of the anti-PD-L1 monoclonal antibody, Atezolizumab, using a (G4S)×3 linker. The antitumor efficacy of B1451 was then evaluated in preclinical models in vitro and in vivo.ResultsOur findings demonstrated a significant positive correlation between the gene expression of PD-L1 and αvβ3 across various human solid tumors. Additionally, high αvβ3 expression appears to influence the sensitivity to immunotherapy. The dual function antibody B1451 was capable of recognizing human PD-L1 and αvβ3 antigens, effectively blocking both the PD-1/PD-L1 and vitronectin/αvβ3 pathways. B1451 inhibited tumor cell migration, adhesion, and angiogenesis in vitro, and exhibited superior anti-tumor activity in vivo than monotherapy.ConclusionThe dual function antibody targeting both αvβ3 and PD-L1 holds the potential to reverse immune evasion and exhibit synergistic anti-tumor effects, offering a promising therapeutic strategy for the treatment of solid tumor.